Improving Early Awareness of Body Organ Health in Students of State Elementary School 01 Pasar Laban Through Interactive Device-Based Education - Fadilaturahmah Fadilaturahmah; Sa’diatul Fuadiyah; Putri Qalbina; Kheniva Diah Anggita; Yusni Atifah; Threo Wanda Marten; Afifatul Achyar; Dwi Hilda Putri; Dezi Handayani; Defni Yannita (Fakultas MIPA Universitas Negeri Padang, 2026)
The health of elementary school-aged children is a crucial factor that needs attention. However, the low awareness of students, especially at SDN 01 Pasar Laban, regarding the importance of maintaining healthy body organs is a problem that needs to be addressed immediately. One of the causes is the limited interactive learning methods in schools, especially regarding body organ health. Therefore, an innovative approach is needed in health education for students, namely a learning method based on interactive teaching aids